Idiopathic Cavernosal Abscess: An Uncommon Case Report - Simões de Oliveira, Pedro (2018)
Cavernosal abscess is an uncommon condition. It can be idiopathic or with an underlying cause. Surgical drainage and systemic antibiotics remain the first line of treatment regarding long-term sequelae. The authors report a rare case of a 51-year-old man with a bilateral cavernosal abscess with no underlying cause. The patient was treated with surgical drainage and systemic antibiotics. Culture of pus was positive for Staphylococcus aureus. There were no sequelae at six-month follow-up.